Babies - Heiligman, Deborah; Freeman, Laura (Washington : National Geographic Society, 2002)
Describes how babies look and act and how they change as they grow.
Accelerated Reader AR
Keywords: Infants -- Development -- Juvenile literature; Infants -- Growth -- Juvenile literature; Babies